2016
DOI: 10.1021/acsinfecdis.6b00058
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Biochemical Characterization of Acinetobacter spp. Aminoglycoside Acetyltransferases Highlights Functional and Evolutionary Variation among Antibiotic Resistance Enzymes

Abstract: Modification of aminoglycosides by N-acetyltransferases (AACs) is one of the major mechanisms of resistance to these antibiotics in human bacterial pathogens. More than 50 enzymes belonging to the AAC(6') subfamily have been identified in Gram-negative and Gram-positive clinical isolates. Our understanding of the molecular function and evolutionary origin of these resistance enzymes remains incomplete. Here we report the structural and enzymatic characterization of AAC(6')-Ig and AAC(6')-Ih from Acinetobacter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…The AAC(6’)-I enzymes can be divided into three sub-families, based upon their structural and kinetic properties 15 16 . The AAC(6’)-Ie and AAC(6’)-Ib enzymes are classified together in sub-family C, whose members are all monomeric enzymes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AAC(6’)-I enzymes can be divided into three sub-families, based upon their structural and kinetic properties 15 16 . The AAC(6’)-Ie and AAC(6’)-Ib enzymes are classified together in sub-family C, whose members are all monomeric enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…The AAC(6’)-Ig, AAC(6’)-Ih and AAC(6’)-Iy enzymes are in sub-family A and are domain-swapped dimers, with the C-terminal β-strand from one protein chain inserted between two strands from the neighboring molecule. The close proximity of the two protein chains in the dimer brings each monomer close enough such that a loop from one monomer forms part of the other chain’s active site, and vice versa 16 . The AAC(6’)-Ii enzyme is currently the sole member of sub-family B, and although this enzyme is also dimeric, the oligomer formed is different from the subfamily A dimer.…”
Section: Introductionmentioning
confidence: 99%
“…5, asterisks under red highlight) that led to variants with decreased affinity for streptothricin ( Table 2), suggesting that this area is part of the structure where SatA binds streptothricin. Recently, Stogios et al showed that the antibiotic tobramycin binds to 6=-N-acetyltransferase [AAC(6=)-Ib] in an open cleft (30), highlighting the possibility that streptothricin binds to this region of SatA. We introduced substitutions at positions Y149, F154, and Y164 using the B. anthracis satA ϩ allele by site-directed mutagenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to our understanding of AcCoA binding, how GNATs bind their cosubstrate is less known. Recently, Stogios et al conducted an in-depth study of how the GNAT AAC(6=)-Ig binds aminoglycosides (30). In the structure of the AAC(6=)-Ig/tobramycin complex, nine residues were found to bind the antibiotic.…”
Section: Discussionmentioning
confidence: 99%
“…3B). Proteins from the same subfamily of aminoglycoside acetyltransferases as AAC6 exist as homodimers, with the C-terminal β-strand of one protein chain inserted between two strands of the other chain ( 26 ) . We also discern these dimer interactions among the top-ranked inferred residue-residue contacts (Fig.…”
Section: Figure 1 Approach: From Laboratory Evolution Experiments Tomentioning
confidence: 99%